Use of Trails as a Geoconservation Strategy - Guimarães, Thaís de Oliveira; Mariano, Gorki (Anuário do Instituto de Geociências, 2017)
Geoconservation aims to protect areas of relevant geologic interest. It is endowed with oriented tools such as conservation and dissemination of natural abiotic elements. Geotourism emerges in this context, as a leisure activity based on the principles of geodiversity, which is a part of tourism with emphasis on geological monuments. Based on these aspects and considering his relevance to ilustrate the evolutionary history of Earth, it is important to conduct studies that describe, analyze, and stablishes measures for conservation and management of potential geoturistic areas, taking into account their vulnerability and other peculiarities. This work has as the main goal to encourage the dissemination, valorization and conservation of natural abiotic heritage by mapping, describing and classifying trails. It presents proposals focused on conservation of geological features derived from Earth's Geodynamics in order to improve the infrastructure for walking routes, and prepare material of information printed and digital media. Thus, it is intended to build a sense of responsibility concerning non-renewable natural monuments of the planet and also present suggestions that reduce geological risks related to the tourism activity.